Membranes composed of poly(lactic acid)/poly(ethylene glycol) and Ora-pro-nóbis (Pereskia aculeata Miller) extract for dressing applications - Mendes, Juliana Farinassi; de Lima Fontes, Marina [UNESP]; Barbosa, Talita Villa; Paschoalin, Rafaella T.; Mattoso, Luiz Henrique Capparelli (Elsevier, 2024)
Wounds are considered one of the most critical medical conditions that must be managed appropriately due to the psychological and physical stress they cause for patients, as well as creating a substantial financial burden on patients and global healthcare systems. Nowadays, there is a growing interest in developing nanofiber mats loaded with varying plant extracts to meet the urgent need for advanced wound ressings. This study investigated the development and characterization of poly(lactic acid) (PLA)/ poly(ethylene glycol) (PEG) nanofiber membranes incorporated with Ora-pro-nóbis (OPN; 12.5, 25, and 50 % w/w) by the solution-blow-spinning (SBS) technique. The PLA/PEG and PLA/PEG/OPN nanofiber membranes were characterized by scanning electron microscopy (SEM), thermal properties (TGA and DSC), Fourier transform infrared spectroscopy (FTIR), contact angle measurements and water vapor permeability (WVTR). In addition, the mats were analyzed for swelling properties in vitro cell viability, and fibroblast adhesion (L-929) tests. SEM images showed that smooth and continuous PLA/PEG and PLA/PEG/OPN nanofibers were obtained with a diameter distribution ranging from 171 to 1533 nm. The PLA/PEG and PLA/PEG/OPN nanofiber membranes showed moderate hydrophobicity (~109–120°), possibly preventing secondary injuries during dressing removal. Besides that, PLA/PEG/OPN nanofibers exhibited adequate WVTR, meeting wound healing requirements. Notably, the presence of OPN gave the PLA/PEG membranes better mechanical properties, increasing their tensile strength (TS) from 3.4 MPa (PLA/PEG) to 5.3 MPa (PLA/PEG/OPN), as well as excellent antioxidant properties (Antioxidant activity with approximately 45 % oxidation inhibition). Therefore, the nanofiber mats based on PLA/PEG, especially those incorporated with OPN, are promising options for use as antioxidant dressings to aid skin healing.
Keywords: Antioxidant activity; Cell viability; Nanofibers; Solution-blow-spinning (SBS); Swelling tests; Tissue engineering